Collective Social Awareness of COVID-19 and the Challenges in Facing It from Islamic Perspective - Al-Ajmi Euchi, Ali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This study explores key questions related to the COVID-19 pandemic and the Islamic position on it. The significance of this research lies not only in the different answers it provides regarding this issue, but also in the questions it coins to win the bet of waking the collective social consciousness and convincing it of the necessity of Islam in such circumstances as a guide and guard of human stability. This research pursues an analytical methodology that is partly deconstructive and partly historical as it traces the positions Islam took in response to epidemics based on the collective consciousness of the society in its specific historical context. It is the goal of this study to develop an understanding of the way religion responds to pandemics and its ability to help overcome its negative impact through unique intellectual and creedal powers that lie in its foundational fundamentals. The main result of the research is that Islamic jurisprudence and its purposes are strongly present and are some of the most important factors of intellectual advancement in facing the most important developments in the reality of the human being.